The origins and growth of the Meatless Monday movement - Semba, Richard D.; Neu, Peggy; Berg, Pamela; Harding, Jamie; McKenzie, Shawn; Ramsing, Rebecca (Frontiers in Nutrition, 2024)
Meatless Monday is a global movement that encourages people to reduce meat in their diets for their own health and the health of the planet. We conducted a comprehensive review of primary and secondary sources and archival material documenting the origins, historical roots, and growth of Meatless Monday and simultaneous developments in public health. Sources for the paper included publications of the US Food Administration and articles and media identified using searches of ProQuest Historical Newspapers, Newspapers.com Academic, ProQuest US Newsstream, ProQuest Canadian Newstream, ProQuest International Newsstream databases, and Google.com. Meatless Monday was conceived by the advertising executive and public health advocate Sid Lerner in 2003, inspired by the meatless days observed during World War I and II. Meatless Monday grew steadily from 2003 to 2023 through advocacy by food writers, talk show hosts, and celebrity chefs, and through participation by schools, cities, restaurants, corporations, and institutions worldwide. School systems began to observe Meatless Monday, such as Baltimore City Public Schools in 2009 and New York City Public Schools in 2019. Meat-Free Monday campaign was launched by Paul McCartney and his daughters in 2009 in the UK. The Humane Society of the United States became an advocate for Meatless Monday and helped institute it in >200 US school systems. From 2003 to 2023, Meatless Monday spread to over forty countries and was observed in public schools in countries such as Brazil, Ireland, and Belgium. Findings regarding high meat consumption and its adverse effects on health, high greenhouse gas production and environment degradation, and problems with animal welfare under conditions of industrial food animal production emerged during the same period and influenced many to advocate Meatless Monday. Meatless days of World War I and II were driven by patriotic motivations to provide food for the US troops and the Allies in Europe, whereas motivations for observing Meatless Monday were largely related to concerns regarding personal health, the environment, and animal welfare. Meatless Monday grew from relatively humble origins to a highly recognized worldwide movement with wide appeal as a way to begin reducing meat consumption for personal and planetary health.